Penerapan UPIN (UNO Pintar) Untuk Meningkatkan Fokus dan Motivasi Belajar Siswa di Era Digital Melalui Konsep Flipped Classroom (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the effectiveness of using UPIN (Uno Pintar) media based on the flipped classroom approach in enhancing the focus and learning motivation of eighth-grade students at SMP Negeri 14 Malang. The primary focus of this research is to describe how the integration of UPIN media with the flipped classroom model can strengthen students’ concentration during the learning process and to evaluate its impact on improving learning motivation. A qualitative approach with a case study design was employed, utilizing observation, interviews, questionnaires, and documentation as data collection techniques. The results indicate that the combination of self-directed learning before class and interactive in-class activities through educational games significantly increases student engagement. Students became more focused, enthusiastic, and motivated in participating in lessons, which positively affected their academic performance. The study concludes that the UPIN learning media innovation, integrated with the flipped classroom approach, is effective in creating an active and enjoyable learning environment that fosters motivation and focus among students in the digital age.